Maturity Assessment of Knowledge Management as A Strategic Tool to Engage Generation Z and Enhance Sustainable Operations: A Case Study of Indonesia’s MRO Company - Fahlevi, Mohammad Rheza; Febriansyah, Hary (Syntax Literate, 2025)
PT Garuda Maintenance Facility AeroAsia (GMF) faces challenges in organizational knowledge management due to generational shifts or the retirement of experienced employees and the emergence of Generation Z with different learning preferences. Effective Knowledge Management (KM) is key in maintaining operational continuity, driving innovation, and increasing new generation engagement. This research aims to assess KM maturity at GMF from the perspective of Gen Z employees, identify the specific challenges they face, and provide strategic recommendations for KM improvements that support engagement and sustainability. The research used a case study method with a mixed approach. Quantitative data was obtained through the Asian Productivity Organization (APO) KM Assessment Tool survey, while qualitative data was collected through Focus Group Discussions (FGDs), interviews, analysis of open-ended survey responses, and review of company documents. Analysis was conducted using statistical methods for quantitative data and thematic analysis for qualitative data. Results show that Gen Z rated GMF's KM maturity at Level 4 (“Refinement”), but there are still barriers in knowledge access, relevance of KM content, and lack of alignment with Gen Z's digital and interactive preferences. Cultural barriers also hinder widespread KM adoption. This research proposes a multi-pillar strategy to build a vibrant and inclusive KM ecosystem, and provides a framework that can be replicated by other organizations facing similar challenges.